Safety and efficacy of etanercept and adalimumab in children aged 2 to 4 years with juvenile idiopathic arthritis. Issue 12 (December 2016) - Windschall, D.; Horneff, G.
Abstract The TNF inhibitors etanercept (ETA) and adalimumab (ADA) are approved for treating patients older than 2 years with polyarticular juvenile idiopathic arthritis (JIA). Because long-term experience of treating children younger than 4 years is limited, we evaluated the efficacy and safety of ETA or ADA in patients aged 2–4 years. This prospective, long-term, observational registry study documented baseline demographics, clinical characteristics, disease activity parameters, and safety of patients treated with ETA or ADA. Efficacy was determined using the JADAS-10, the JADAS criteria for minimal disease activity (MDA) and remission, and the PedACR response criteria after 3, 6, 12, 18, and 24 months. Between January 2001 and March 2015, 85 patients with polyarticular JIA aged 2–4 years started anti-TNF-α treatment. Seventy-four (54 girls) patients were treated with ETA and 11 (7 girls) with ADA. After 6/12/24 months of treatment, JADAS-MDA was reached by 55/58/58 % of ETA patients and 50/71/66 % of ADA patients. Furthermore, JADAS-Remission was achieved by 35/44/50 % of ETA patients and 16/28/66 % of ADA patients. PedACR 50/70/90 response was achieved by 64/54/41 % of ETA patients and 56/33/22 % of ADA patients at the last treatment observation. Discontinuation because of remission or inefficacy was recorded in 24 (29 %) and 28 (33 %) patients, respectively. Seventy-nine adverse events and four serious adverse events were reported. Administration of ETA and ADA in JIA patients younger than 4 years was efficacious, well tolerated, and safe. Patients younger than 4 years may show marked improvement following anti-TNF-alpha therapy.